Community Conversations: Stakeholder-Identified Research Priorities to Foster Community Participation for Individuals With Intellectual and Developmental Disability - Bendixen, Roxanna M.; Benevides, Teal; Ideishi, Roger; Smythe, Robert; Taylor, Joshua; Umeda, Caroline; Kerfeld, Cheryl; Jirikowic, Tracy (Frontiers in Rehabilitation Sciences, 2022)
To identify future research priorities and meaningful outcomes focused on community-level interventions for children and youth with intellectual and developmental disabilities and families, a group underrepresented in research, we established a diverse patient-centered outcomes research (PCOR) community. We focused on engaging regionally and nationally-diverse stakeholders—individuals, families, healthcare professionals, community, and policy experts—in research development activities that would build partnerships and research capacity. This community included individuals with intellectual and developmental disabilities, family members, and of stakeholders also who represented the matrix of systems, services, and programs that people frequent in their communities (e.g., cultural arts, worship, sports and recreation, and transportation). We present the engagement process and methods we used are significant for including individuals with intellectual and developmental disabilities as stakeholders in research planning and processes. The results of planning, completing, and evaluating three face-to-face research capacity-building meetings and their subsequent stakeholder engagement activities include: 1) individuals with intellectual and developmental disabilities and their families clearly expressed a desire to be included and to feel good about their participation in community settings, 2) many of our stakeholders wanted action and change to happen in their communities now, and often did not realize or understand that research takes time, 3) organizations expressed a need for mentoring related to best practices for access and inclusive programming. Overarching issues around societal inclusion, equal opportunities, and life chances for individuals with intellectual and developmental disabilities and their families were front and center across communities and multi-stakeholder groups, and achieving change remains valued and a high priority.